3D-printed bioceramic scaffolds for bone defect repair: bone aging and immune regulation - Qi, Haoran; Zhang, Bo; Lian, Feng (Frontiers in Bioengineering and Biotechnology, 2025)
The management of bone defects, particularly in aging populations, remains a major clinical challenge. The immune microenvironment plays an important role in the repair of bone defects and a favorable immune environment can effectively promote the repair of bone defects. However, aging is closely associated with chronic low-grade systemic inflammation, which adversely affects bone healing. Persistent low-grade systemic inflammation critically regulates bone repair through all stages. This review explores the potential of 3D-printed bioceramic scaffolds in bone defect repair, focusing on their capacity to modulate the immune microenvironment and counteract the effects of bone aging. The scaffolds not only provide structural support for bone regeneration but also serve as effective carriers for anti-osteoporosis drugs, offering a novel therapeutic strategy for treating osteoporotic bone defects. By regulating inflammation and improving the immune response, 3D-printed bioceramic scaffolds may significantly enhance bone repair, particularly in the context of age-related bone degeneration. This approach underscores the potential of advanced biomaterials in addressing the dual challenges of bone aging and immune dysregulation, offering promising avenues for the development of effective treatments for bone defects in the elderly. We hope the concepts discussed in this review could offer novel therapeutic strategies for bone defect repair, and suggest promising avenues for the future development and optimization of bioceramic scaffolds.